Identifikasi Faktor Penyebab Hilangya Budaya Adat Istidat di Desa Sekunyit Kaur Selatan - Riyadi, Dayun; Ronalika, Fanisa; Triwuryani, Lulut; Putri Iswandi, Kenari; Hidayatullah, Aldes; Sela, Anada; Bintang, Muhammad; Khasisah, Fitri; Briantoni, Arip; Wulandari, Fetri (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
The factor in the loss of customs is due to promiscuity, loss Religious cultures, on the one hand, play a good and positive role, but on the other hand there are many the negative. For example, a lot of time is wasted, but on the positive side it can be done studying religion, general knowledge on social media, the impact is because it has clearly taken over When finally there was an opportunity to learn about the customs or mores of this village or the problems religion automatically decreases or even disappears. It is very influential because there is a lot of social media which is tempting so the impact was that there was no enthusiasm for old customs, It is very clear that this change in the morals of the people is very far from traditional customs in this village, whether from a village or a religious perspective, in the past, customs were still upheld for example, the teenagers were polite but now they seem to be indifferent, for example when they are told to conveying the invitation so that his clothes already reflect politeness from his greetings, he was very indifferent to saying hello to the point of not even saying hello, Many, one example is that at these events you automatically wear a sarong, but wear a skullcap now they wear trousers, there are also those who don't wear trousers, Alhamdulillah, economic development has increased rapidly, but morals have decreased greatly. Because of modern activities, customs have been abandoned, there are, for example, elections and Leaders say, like priests, there is never a voting system or a democratic system, the system was promator or appointed, but now the system has reached the point where it is like that democracy, No, Because it has no effect. It's just a matter of a new celebration the effect and Very disappointed because, there is no increase but a decrease